Temperamental Development among Preterm Born Children. An RCT Follow-Up Study - Inger Pauline Landsem; Bjørn Helge Handegård; Stein Erik Ulvund (MDPI AG, 2020)
A randomized controlled trial study recruited 146 preterm born children, either to participate in a modified version of the Mother-Infant Transaction Program (MITP-m) or to receive the usual follow-up services, before and after discharge from a neonatal intensive care unit. This follow-up study investigates whether MITP participation is associated with parental perceptions of child temperament from two to seven years. Children's temperament was reported by mothers and fathers separately at children's ages of 2, 3, 5, and 7 years. Parents in the MITP-m group reported lower levels of negative emotionality in their children compared to the control group. In maternal reports, a group effect (F(1, 121) = 9.7, p = 0.002) revealed a stable difference in children's negative emotionality from two to seven years, while a group-by-time interaction related to an increasing difference was detected in reports from fathers (F(1, 94) = 4.8, p = 0.03). Another group difference appeared in fathers' reports of children's soothability (F(1, 100) = 14.2, p < 0.0005). MITP-m fathers seemed to perceive their children as easier to soothe at all ages as no interaction with time appeared. Parental reports on children's sociality, shyness, and activity did not differ between the groups.